(untitled) (Transmediterranean History, 2023)
The trade agreement concluded in 652/1254 between Mamlūk Egypt and the Republic of Venice resulted from a special political situation: during the failed French Crusade of 1249–1250, military slaves known as Mamlūks had taken over rule in Egypt. Under their new, still somewhat insecure sultan al-Malik al-Muʿizz, they reached a first treaty agreement with a European-Christian power. A comparison with an earlier trade agreement concluded in 636/1238 under Ayyūbid rule shows, however, that the crusade and the resulting change of regime in Egypt had done little to change the conditions of Venetian trade. The treaty of 652/1254 can thus be placed in a longer history of bilateral trade relations between Venice and Egypt that is characterised by continuity. It also offers interesting insights into the everyday life of Venetian merchants in Alexandria.